The Effect of Katuk Leaf (Sauropus androgynous L. Merr) Water Extract Through Drinking Water on Protein, Fat, Cholesterol, and Colour of Lohmann Brown Egg Yolks - B. A., Carolin; Sumardani, N. L. G.; Bidura, I G. N. G. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This research aimed to find out the influence of giving katuk leaf ( Sauropus androgynous L. Merr) water extract towards colour, protein levels, fat levels, and the cholesterol of Lohmann Brown chicken egg yolks in the age of 22-30 weeks. This research has been implemented at the poultry farm in Dajan Peken Village, Tabanan sub-district, Tabanan regency through three months. The design of experiment that applied in this research is Completely Randomized Design (CRD) with three treatments and six replications. Those 36 laying chicken of Lohmann Brown with homogeneous weight were raised in 18 squares of colony battery cages. The treatment consisted of drinking water without additional of katuk leaf water extract (K0) as the control, drinking water with addition of 3% katuk leaf water extract (K1), and drinking water with addition of 6% katuk leaf water extract (K2). The colour, protein levels, fat levels, and the cholesterol of egg yolks were the variables that observed in this research. The result showed that the colour of egg yolks and protein levels towards the (K1) and (K2) treatment gave significant effect (P<0,05) higher than K0. However, the fat levels and the cholesterol of egg yolks towards the (K1) and (K2) treatment gave significant effect (P<0,05) lower than the chicken which was not given the addition of katuk leaf ( Sauropus androgynous L. Merr) water extract (K0) as the control. From the result, it can be concluded that the giving katuk leaf ( Sauropus androgynous L. Merr) water extract with addition of  3% and 6% level through drinking water could increase the colour and the protein levels of chicken egg yolks and also the reduction of fat levels and cholesterol of chicken egg yolks of Lohmann Brown in the age of 22-30 weeks were occurred. Keywords: katuk leaf water extract, egg yolk, Lohmann Brown chicken